Effectiveness of Academic Administration in the 21st century of Schools Under Chaiyaphum Primary Educational Service Area Office 1: ประสิทธิผลการบริหารงานวิชาการในศตวรรษที่ 21 ของโรงเรียนสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาชัยภูมิ เขต 1 - Nueangnongkhu, Phimphisa; Sukserm, Pannapa (Journal of Graduate MCU KhonKaen Campus, 2022)
This research aims to 1) to study Effectiveness of academic administration in the 21st century of schools under Chaiyaphum Primary Educational Service Area Office 1 According to the opinions of the director of the educational institute and government teacher (2) to compare Effectiveness of academic administration in the 21st century of schools under Chaiyaphum Primary Educational Service Area Office 1 Classified by working position and (3) to study recommendations Guidelines for the development of academic administration in the 21st century effective school under Chaiyaphum Primary Educational Service Area Office 1 The sample groups used in this study were: school director and government teachers under Chaiyaphum Primary Educational Service Area Office 1 year 2021. Number of 327 people. By studying all 6 areas, namely (1) Curriculum development for educational institutions (2) Learning process development (3) Evaluation, evaluation and comparison of the transfer of learning results (4) Research for improving the quality of education (5) Educational supervision and (6) the development of innovative media and educational technology. data analysis results The overall picture is at a high level. ( = 3.53, S.D. = .05) When considering each aspect, it was found that Effectiveness of academic administration in the 21st the most is Research for improving the quality of education ( = 3.62, S.D. = .32) and the least side Educational supervision ( = 3.44, S.D. = .42)